PENGARUH PEMBERIAN JUS LIDAH BUAYA TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS - Agustina Simamora; Icceng Icceng (Jurnal Penelitian Keperawatan Medik, 2018)
Diabetes mellitus is a disease caused by the generation of high blood sugar levels. The treatment of diabetes mellitus is usually with weight control, diet, exercise, and pharmacologis treatment with the drug. One treatment in an alternative way, namely with aloe vera juice can lower blood sugar levels. The purpose of reasearch was to identify the effect of aloe vera juice to decrease blood sugar levels in people with diabetes mellitus at sub village IV village marindal sub district patumbak district deli serdang. The design used is design pre - post without control. The total population is 50 respondents. Sampling techniques used is the formula notoadmojho 10% with a sample of five samples. Independent variables prior to the giving of aloe vera and the dependent variable was after the administering aloe vera. Analysis of the data used T test. From the results, a significant value pvalue = 0.001 which means there is the effect of aloe vera juice to decrease blood sugar levels in people with diabetes mellitus .There is a significant reduction in blood sugar levels of 166.373 mg / dl after administering juice aloe vera 150 gr per day during 7 days.